Beryllium bis(diazaborolyl): old neighbors finally shake hands. Issue 4 (24th November 2014) - Arnold, T.; Braunschweig, H.; Ewing, W. C.; Kramer, T.; Mies, J.; Schuster, J. K.
Abstract : The synthesis of a linear beryllium bis(diazaborolyl) compound featuring the first non-cluster bond between boron and beryllium has been achieved through the reaction of Yamashita's lithium diazaborolide and BeCl2 . Abstract : The synthesis of a linear beryllium bis(diazaborolyl) compound featuring the first non-cluster bond between boron and beryllium has been achieved through the reaction of Yamashita's lithium diazaborolide and BeCl2 . In accord with the established chemistry of beryllium, the bonding is polar covalent in character, as determined by structural and spectroscopic analysis, as well as reactivity studies.